Effectiveness of Integrated Physical Exercise Program on Physical Function, Metabolic Health, and Quality of Life in Pre-Elderly With Musculoskeletal Complaints - Widanti, Herista Novia; Dwi Yuliani, Resta; Anjasmara, Bagas (JURNAL PROFESIONAL FISIOTERAPI, 2026)
Introduction: Musculoskeletal complaints are prevalent among pre-elderly individuals, affecting physical function, increasing metabolic risks, and reducing quality of life. Structured and integrated exercise programs tailored for this population remain limited. Objective: This study aimed to evaluate the effects of an Integrated Physical Exercise Program (IPEP) on physical function, metabolic parameters, and quality of life in a pre-elderly individual with musculoskeletal complaints. Methods: A single-subject (N-of-1) design was used. A 46-year-old woman participated in an eight-week IPEP conducted at the Sports Physiotherapy Laboratory of Universitas Muhammadiyah Sidoarjo. Assessments included balance, muscle strength, flexibility, cardiorespiratory fitness, metabolic markers, musculoskeletal symptoms, and quality of life. Results: After the intervention, improvements were observed in balance, muscle strength, flexibility, and VO₂max. Metabolic indicators such as blood pressure, glucose, cholesterol, and uric acid showed favorable changes. Musculoskeletal pain areas decreased, and quality of life scores increased, particularly in physical and psychological domains. Conclusion: The IPEP was effective in enhancing physical function, metabolic health, and quality of life in a pre-elderly individual with musculoskeletal issues. This program has potential as a feasible community-based preventive strategy.